Developing a 'clinical' model for teacher education - Conroy, J; Hulme, M; Menter, I (2013)
This paper reports on the introduction of a 'clinical model' of teacher education at the University of Glasgow in 2011. The account is set against the backdrop of a review of major contemporary developments in teacher education. The common focus in this work is on such themes as the key function of the practicum, on 'teaching schools' and on the roles and responsibilities of the various players in teacher professional learning. The context for reform of teacher education in Scotland is described, showing how the opportunity for a radical intervention arose. The distinctive features of the Glasgow model are set out and a summary of the findings of the internal evaluation carried out at the University is offered. Issues identified include challenges of communication, the nature of professional learning and the cultural embeddedness of existing practices. In the light of this initiative, the paper then reviews insights gained concerning the relationship between policy, practice and research in teacher education, before concluding with comments on the future of research in teacher education. © 2013 © 2013 Taylor and Francis.